Electrochemical Study for using Eg-Dronate Drug as a Green Corrosion Inhibitor in 0.5 M H2SO4 Solution by Applied: Potentiodynamic and Evans Techniques (London Journal of Research In Science: Natural and Formal, 2023)
In this paper usingthe Egy-dronate pharmaceutical drug compound as a green corrosion inhibitor that can decreasing the rate of corrosionon metallic surface, as a result of the  adsorption of Egy-dronateon the metal surface. In this regard, we simultaneously present an overview of Egy-dronate compound performance, as a corrosion inhibitor in 0.5 M H2SO4, and with presence different concentrations of the drug. By using potentiodynamic polarization, and Evans techniques illustrate the nature of adsorption, the effect of medium on the corrosion processes, and the effect of polarization for the orientation of the inhibitor molecule to the CS surface. The surface examination by Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX), Atomic Force Microscopy (AFM), and Fourier Transforms Infrared (FT-IR)are confirmed the formation thin film that adsorbed on the metal surface according to the mechanism of the adsorption processes on the polarized metal surface.
Keywords: corrosion inhibition; potentiodynamic polarization; evans technique; egy-dronate inhibitor; SEM; EDX; AFM; FT-IR